INCREASING KNOWLEDGE ABOUT STUNTING AND TRAINING CADRES IN MAKING ANTI-STUNTING PMT FROM SNAKEHEAD FISH - Muhammad Fifin Kombih; Wiwik Winarningsih; Dewi Masithah; Rizki Nurmalya Kardina; Fatan Danish Zamzamy; Eka Satria Akbar; Farid Adandi Hakim; Febriaulia Nastasha Romli1; Nur Rahma; Nadia Suryani; Retno Diah Putri Ekayanti (Community Service Journal of Indonesia, 2026)
Stunting not only affects a child's physical condition but also their cognitive development and long-term performance due to suboptimal brain development. The most crucial intervention in addressing stunting occurs during the first 1,000 days of life (HPK). Providing adequate food intake and good nutrition doesn't have to be expensive. One effort that can be made is by providing a PMT (Food Supplement) made from snakehead fish. Snakehead fish is good for consumption by anyone, including toddlers and pregnant women. 100 grams of snakehead fish contains 80 calories and various beneficial nutrients needed by the body. In addition to these nutrients, snakehead fish also contains carbohydrates, iron, copper, vitamin B2, and omega-3 fatty acids. The nutrient-rich content of snakehead fish can be an alternative to high-calorie PMT ingredients. Based on the results of an initial survey conducted by the proposal team, it turns out that many male and female students at Zainul Hasan Genggong Islamic Boarding School still lack a good understanding of stunting and how to prepare anti-stunting supplementary foods. Based on these findings, the proposal team plans to conduct community service activities. The methods used in this community service activity were counseling on stunting and training in making anti-stunting PMT from snakehead fish. The results of the activity showed an 85% increase in knowledge after the counseling. In addition, the training successfully improved the skills of male and female students in processing snakehead fish into various simple and nutritious PMT preparations. The enthusiasm of the participants was evident from their active participation in discussions and direct involvement in the PMT preparation practice. Conclusion: Education on stunting combined with training in making PMT from snakehead fish has proven effective in increasing the knowledge and skills of students. The high nutritional content of snakehead fish makes it a potential alternative to support stunting prevention in the community.